High SARS-CoV-2 infection rate after resuming professional football in São Paulo, Brazil - Gualano, B.; Mendes Brito, G.; Pinto, A. J.; Ribeiro Lemes, I.; Nagem Janot Matos, L. D.; de Sá Pinto, A. L. (British Journal of Sports Medicine, 2022)
Objective To examine the SARS-CoV-2 infection rate in a cohort of 6500 professional athletes and staff during the 2020 football (soccer) season in São Paulo, Brazil.